Advances in Our Clinical Understanding of Autonomic Regulation Therapy Using Vagal Nerve Stimulation in Patients Living With Heart Failure - Konstam, Marvin A.; Mann, Douglas L.; Udelson, John James E.; Ardell, Jeffrey L.; De Ferrari, Gaetano M.; Cowie, Martin R.; Klein, Helmut U.; Gregory, Douglas D.; Massaro, Joseph M.; Libbus, Imad; DiCarlo, Lorenzo A.; Butler, Javed; et al. (Frontiers in Physiology, 2022)
The ANTHEM-HF, INOVATE-HF, and NECTAR-HF clinical studies of autonomic regulation therapy (ART) using vagus nerve stimulation (VNS) systems have collectively provided dose-ranging information enabling the development of several working hypotheses on how stimulation frequency can be utilized during VNS for tolerability and improving cardiovascular outcomes in patients living with heart failure (HF) and reduced ejection fraction (HFrEF). Changes in heart rate dynamics, comprising reduced heart rate (HR) and increased HR variability, are a biomarker of autonomic nerve system engagement and cardiac control, and appear to be sensitive to VNS that is delivered using a stimulation frequency that is similar to the natural operating frequency of the vagus nerve. Among prior studies, the ANTHEM-HF Pilot Study has provided the clearest evidence of autonomic engagement with VNS that was delivered using a stimulation frequency that was within the operating range of the vagus nerve. Achieving autonomic engagement was accompanied by improvement from baseline in six-minute walk duration (6MWD), health-related quality of life, and left ventricular EF (LVEF), over and above those achieved by concomitant guideline-directed medical therapy (GDMT) administered to counteract harmful neurohormonal activation, with relative freedom from deleterious effects. Autonomic engagement and positive directional changes have persisted over time, and an exploratory analysis suggests that improvement in autonomic tone, symptoms, and physical capacity may be independent of baseline NT-proBNP values. Based upon these encouraging observations, prospective, randomized controlled trials examining the effects on symptoms and cardiac function as well as natural history have been warranted. A multi-national, large-scale, randomized, controlled trial is well underway to determine the outcomes associated with ART using autonomic nervous system engagement as a guide for VNS delivery.